2020
DOI: 10.7150/ijbs.38214
|View full text |Cite
|
Sign up to set email alerts
|

LRRC75A antisense lncRNA1 knockout attenuates inflammatory responses of bovine mammary epithelial cells

Abstract: Long noncoding RNAs (lncRNAs) play multiple key roles during inflammatory processes. In this study, a novel lncRNA identified by the high-throughput sequencing analysis was found significantly down-regulated in Escherichia coli-introduced cell model of bovine mastitis. Given that this lncRNA consists of the antisense of leucine-rich repeat-containing protein 75A (LRRC75A), it was named LRRC75A antisense lncRNA1 (LRRC75A-AS1). The expression of LRRC75A-AS1 was down-regulated in bovine mammary epithelial cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…There have been research evidences that lncRNA plays a key role in mastitis caused by S. aureus , Escherichia coli , Mycoplasma bovis , and other pathogens though regulating the expression of specific genes. LRRC75A-AS1 in bovine mammary epithelial cells and breast tissue was downregulated under inflammatory conditions, and knocking out LRRC75A-AS1 in MAC-T cell line inhibited the adhesion and invasion of S. aureus and attenuated the activation of the NF- κ B pathway [ 12 ]. LncRNA-TUB was the higher expression in the mammary epithelial cells of dairy cows that received proinflammatory stimulation, and knockout of lncRNA-TUB indicated that it played a key role in the morphology, proliferation, migration, and β -casein secretion of mammary epithelial cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been research evidences that lncRNA plays a key role in mastitis caused by S. aureus , Escherichia coli , Mycoplasma bovis , and other pathogens though regulating the expression of specific genes. LRRC75A-AS1 in bovine mammary epithelial cells and breast tissue was downregulated under inflammatory conditions, and knocking out LRRC75A-AS1 in MAC-T cell line inhibited the adhesion and invasion of S. aureus and attenuated the activation of the NF- κ B pathway [ 12 ]. LncRNA-TUB was the higher expression in the mammary epithelial cells of dairy cows that received proinflammatory stimulation, and knockout of lncRNA-TUB indicated that it played a key role in the morphology, proliferation, migration, and β -casein secretion of mammary epithelial cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…They can interact with coding genes in both cis and trans manners to fulfill their functions [ 40 ]. It was found that a new lncRNA, LRRC75A-AS1, could protect its maternal gene ( LRRC75A ) from being degraded and promote inflammation [ 41 ]. Therefore, we performed KEGG and GO analyses to predict the functions of lncRNAs based on the functions of the maternal genes.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging reports has revealed that LRRC75A-AS1 was involved in several biological processes through modulation of signaling pathway, Jeong et al [13] reported that LRRC75A-AS1 can regulate the vascular calcification negatively, and might act as a possible target in the treatment of vascular calcification. Wang et al [14] found that LRRC75A-AS1 can regulate the expression of tight junction (TJ) proteins through LRRC75A, affecting the inflammatory responses of bovine mammary epithelial cells. Leavey K et al [15] show that LRRC75A is abnormally expressed in the process of normal villous maturation.…”
Section: Discussionmentioning
confidence: 99%